2017
DOI: 10.3906/sag-1601-38
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of epidemiology and risk factors for mortality in ventilator-associated pneumonia attacks in intensive care unit patients

Abstract: This retrospective observational study was conducted at the medical/surgical ICU of Ankara Numune Research and Training Hospital for the period of January 2010 to June 2015. This hospital is a referral hospital and there were Background/aim: The aim of this study was to investigate the epidemiologic characteristics, the causative microorganisms and their antimicrobial susceptibility patterns, and the prognostic risk factors for mortality in critically ill patients with ventilator-associated pneumonia (VAP). Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 20 publications
4
22
0
3
Order By: Relevance
“…A mortalidade bruta geral na UTI durante o estudo foi de 34,55%. Um estudo retrospectivo realizado na Turquia em UTI clínica e cirúrgica geral, com 417 pacientes, apontou uma mortalidade bruta de 39,8% nos pacientes com pneumonia associada à ventilação mecânica (17) . Istosugere o fato de que pacientes oncológicos não apresentam mortalidade significativamente superior quando comparados a pacientes internados emUTIs de especialidades diferentes.…”
Section: Discussionunclassified
“…A mortalidade bruta geral na UTI durante o estudo foi de 34,55%. Um estudo retrospectivo realizado na Turquia em UTI clínica e cirúrgica geral, com 417 pacientes, apontou uma mortalidade bruta de 39,8% nos pacientes com pneumonia associada à ventilação mecânica (17) . Istosugere o fato de que pacientes oncológicos não apresentam mortalidade significativamente superior quando comparados a pacientes internados emUTIs de especialidades diferentes.…”
Section: Discussionunclassified
“…A. baumannii is the most common nosocomial pathogen that causes bloodstream infections (BSI) or ventilator-associated pneumonia (VAP) in many medical centers, particularly in Turkey (2, 5). Carbapenem resistance rates exceed 90% in some parts of the World (3).…”
Section: Discussionmentioning
confidence: 99%
“…Eravacycline is a novel fluorocycline that belongs to the tetracycline class of antimicrobials may be a treatment option for CRAB (5). In vitro studies were shown that eravacycline minimum inhibitory concentrations (MICs) were found to be 2-8 fold lower than tigecycline MICs against CRAB (68).…”
Section: Introductionmentioning
confidence: 99%
“…The increasing prevalence of VAP in recent years has made VAP -related health risks a global concern. The incidence rates of VAP in the United States, Europe, Latin America, and Asia Paci c were 13.50%, 19.40%, 13.80%, and 16.00% respectively in a prospective observational study (P = 0.04) [6].The mortality rate of VAP is high, ranging from 14.00% to 44.40%, and can reach 78.00% in speci c settings [8][9][10][11][12]. VAP was shown to prolong the ICU length of stay and increase the risk of death in critically ill patients [13].…”
Section: Introductionmentioning
confidence: 96%